Morphological Changes In Wesakin Village Along The Edge Of "Uwe" River Jayawijaya Regency Papua Mountains Province Indonesia - Soni, Aprianto; YM, Hardiyanti (Jurnal Wilayah dan Kota, 2023)
Wesakin Village, Wouma District, is an area located on the banks of the " Uwe" river. Rivers are very important for the survival of the people living in the village. The " Uwe" river should be preserved but the current situation is the opposite. The preservation of the “ Uwe” river has received little attention from the government, whether in terms of transportation facilities, residential facilities or infrastructure in accelerating regional development. Wesakin Village has been one of the areas affected by natural disasters since in the last 5 years, the impact of this phenomenon resulted in damaged infrastructure. This research uses qualitative methods, while data collection techniques in this research include observation, interviews, documentation and literature study. The results of this research show that there are morphological changes in the residential area on the banks of the “ Uwe” river, which used to be just an ordinary river bank, but as time goes by, there is residential development where the banks of the " Uwe" river, settlements are now starting to become disorganized due to natural disasters such as landslides and flash floods. which once affected Wesakin Village. There are two morphological changes, namely morphological changes in community residential areas and natural morphological changes that occur in changes in the structure of soil and rocks. Keywords: Rivers,Jayawijaya; Landslides; Morphology; Infrastructure.